Exploration of Ethnomathematics On Cakalele Dance Banda Naira and Its Application in Mathematics Learning - Tabien, Hamza; Upu, Hamzah; Bustang, Bustang (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
The study aimed to explore the correlation between mathematics and culture in the Cakalele dance and its application into mathematics learning. This research was exploratory research, utilizing ethnographic methods. The subjects consisted of six people, where five people were from Kampung Baru village, Kecamatan Banda subdistrict (three dancers and trainers, one traditional expert, and one community leader) and with one mathematics teacher from SMP Negeri 34 Central Maluku. The research findings on Cakalele dance culture reveal elements such as types of movements, attire and accessories, weaponry and musical instruments, displays, all incorporating mathematical concepts such as lines and angles, triangles and quadrilaterals, spatial shapes, and geometric transformations. Mathematical elements found in the Cakalele dance can be applied in education by utilizing musical instruments and kapseti as contextual objects to teach the shapes of cylinders and cones to 9th grade junior high school students. The use of movements like (bunga), salawaku, gestures, and gong as teaching media for geometric transformations supports realistic and contextual outdoor learning experiences.